2023
DOI: 10.1097/grf.0000000000000782
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Hemorrhage—Epidemiology, Risk Factors, and Causes

Abstract: The incidence of postpartum hemorrhage (PPH) is increasing worldwide and in the United States. Coinciding, is the increased rate of severe maternal morbidity with blood transfusion in the United States over the past 2 decades. Consequences of PPH can be life-threatening and carry significant cost burden to the health care system. This review will discuss the current trends, distribution, and risk factors for PPH. Causes of PPH will be explored in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The demographic characteristics and preoperative comorbidities of the patients were extracted using data from preoperative evaluation records stored as electronic medical records. The risk factors for PPH including old age of the mother (>35 years), obesity before pregnancy (body mass index [BMI] >30 kg/m 2 ), known coagulation defects, high parity (≥3), nulliparity, history of PPH, abnormal location of placenta (accreta, increta, percreta, or previa), intrapartum bleeding, intrapartum use of magnesium sulfate, delayed delivery, polyhydramnios, twins or multiple gestations, and macrosomia, were collected [ 10 , 11 ]. Anesthesia records were reviewed to determine the number of uterotonic agents administered to each patient during surgery.…”
Section: Methodsmentioning
confidence: 99%
“…The demographic characteristics and preoperative comorbidities of the patients were extracted using data from preoperative evaluation records stored as electronic medical records. The risk factors for PPH including old age of the mother (>35 years), obesity before pregnancy (body mass index [BMI] >30 kg/m 2 ), known coagulation defects, high parity (≥3), nulliparity, history of PPH, abnormal location of placenta (accreta, increta, percreta, or previa), intrapartum bleeding, intrapartum use of magnesium sulfate, delayed delivery, polyhydramnios, twins or multiple gestations, and macrosomia, were collected [ 10 , 11 ]. Anesthesia records were reviewed to determine the number of uterotonic agents administered to each patient during surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Postpartum hemorrhage can have many different causes. Causes of postpartum hemorrhage usually include uterine atony, trauma-related lacerations, placental retention, and bleeding diathesis [3]. Preec-lampsia, placenta accreta spectrum, placenta previa, and multiple pregnancies also increase the likelihood of hemorrhage [4].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] The incidence of PPH has increased in the last decades, likely due to increased maternal age and in vitro fertilization pregnancies, particularly in high-income countries. [13][14][15] Despite adequate prevention, 10,16 PPH can lead to life-saving postpartum hysterectomy when medical and surgical strategies fail to control massive uterine bleeding. 17 Recently, Martone et al suggested a potential relationship between PPH and adenomyosis, 18 outlining mechanisms involved in the pathogenesis, such as altered myometrial contraction, fibrinolysis inhibition, increased angiogenesis, and defective junctional zone modification.…”
Section: Introductionmentioning
confidence: 99%